2008
DOI: 10.1093/toxsci/kfn262
|View full text |Cite
|
Sign up to set email alerts
|

JP-8 Induces Immune Suppression via a Reactive Oxygen Species NF-κβ–Dependent Mechanism

Abstract: Applying jet fuel (JP-8) to the skin of mice induces immune suppression. JP-8-treated keratinocytes secrete prostaglandin E(2), which is essential for activating immune suppressive pathways. The molecular pathway leading to the upregulation of the enzyme that controls prostaglandin synthesis, cyclooxygenase (COX)-2, is unclear. Because JP-8 activates oxidative stress and because reactive oxygen species (ROS) turn on nuclear factor kappa B (NF-kappabeta), which regulates the activity of COX-2, we asked if JP-8-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 36 publications
(55 reference statements)
1
3
0
Order By: Relevance
“…Further, linoleic acid was found to suppress the mitogen-stimulated proliferative responses of human T lymphocytes and murine T and B lymphocytes (Tezabwala et al, 1995). Finally, in vivo studies in humans demonstrated that increased intake of linoleic acid elevates production of prostaglandin E2 (PGE2) (Kelley, 2001), which is consistent with the effects of dermal JP-8 exposure on ROS and PGE2 production reported by Ramos et al (2004, 2009). Because DCI-4A is present in JP-8 at a 1:66,660 dilution (AFLMA, 2007), the concentration of dilinoleic acid in JP-8 is extremely low.…”
Section: Discussionsupporting
confidence: 69%
“…Further, linoleic acid was found to suppress the mitogen-stimulated proliferative responses of human T lymphocytes and murine T and B lymphocytes (Tezabwala et al, 1995). Finally, in vivo studies in humans demonstrated that increased intake of linoleic acid elevates production of prostaglandin E2 (PGE2) (Kelley, 2001), which is consistent with the effects of dermal JP-8 exposure on ROS and PGE2 production reported by Ramos et al (2004, 2009). Because DCI-4A is present in JP-8 at a 1:66,660 dilution (AFLMA, 2007), the concentration of dilinoleic acid in JP-8 is extremely low.…”
Section: Discussionsupporting
confidence: 69%
“…Studies of dermal application of jet fuel in mice have been interpreted as indicating immune suppression (Ramos et al, 2009;Ullrich, 1999;Ullrich & Lyons, 2000). A dermal study in female Sprague-Dawley rats, however, found jet fuel to lack immunotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that through involvement in the transcription of a variety of cytokine genes, NF-κβ could exert a complicated impact on the regulating network. Activated NF-κβ can enhance the transcription of many cytokines, such as TNF-α and IL-1, [ 19 ], to lengthen the synthesizing time and quantity of inflammation factors [ 20 ]. Inhibition of NF-κβ activity can decrease the expression of inflammatory media regulated by NF-κβ, and reduce the infiltration and activation of inflammatory cells, thus protecting lung tissues from damage [ 21 ].…”
Section: Discussionmentioning
confidence: 99%